Plant usage in landscape design [videorecording] (California, CA. : San Luis Video Pubs., 2004)
Explore the importance of plants in the planned landscape, and look into their functional value, aesthetic value, property value and environmental value. Learn about: site analysis, maintenance plans, the function and utility of a site, aesthetics, space articulation, privacy, circulation, screening, views and vista controls, erosion control, soil building, habitat for wildlife, people, historic, cultural influences in landscape design. Source : McIntyre Media Inc. webpage